2018
DOI: 10.1111/zph.12467
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of Shiga toxin‐producing O113:H21 isolates from cattle and meat

Abstract: The serotype O113:H21 is considered one of the relevant non-O157 STEC serotypes associated with severe human infections. Due to the increased detection of O113 strains and their relationship with clinical cases, which emphasizes the importance of this serogroup as an emerging pathogen, our aim was to determine the characteristics of STEC O113:H21 strains circulating in bovine cattle and retail meat from Argentina. For this purpose, we determined the presence and combinations of various virulence genes (and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…This serotype, together with serotypes O130:H1 and O174:H21, have been the most frequently detected among STEC strains in food, dairy cows, beef abattoirs, beef carcasses and cuts and trimmings in slaughterhouses in South American countries (Torres et al., 2018). Furthermore, all the identified serotypes have been associated with human infections (Alonso et al., 2016; Cadona et al., 2016; González‐Escalona & Kase, 2019; Miko et al., 2013; Sanso et al., 2018). In Chile, the most frequently isolated serogroups from human clinical samples belong to O157 and O26 serogroups, whereas O113:H21 has been the most frequently detected in food (ISP, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This serotype, together with serotypes O130:H1 and O174:H21, have been the most frequently detected among STEC strains in food, dairy cows, beef abattoirs, beef carcasses and cuts and trimmings in slaughterhouses in South American countries (Torres et al., 2018). Furthermore, all the identified serotypes have been associated with human infections (Alonso et al., 2016; Cadona et al., 2016; González‐Escalona & Kase, 2019; Miko et al., 2013; Sanso et al., 2018). In Chile, the most frequently isolated serogroups from human clinical samples belong to O157 and O26 serogroups, whereas O113:H21 has been the most frequently detected in food (ISP, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Mellmann et al, 2008;Käppeli et al, 2011). Studies in Argentina showed that STEC O113:H21 has been isolated also from beef and cattle, and it has been recently isolated from humans, pointing out that this is an emerging serotype in the country (DebRoy et al, 2004;Cadona et al, 2016;Sanso et al, 2018). Studies in Brazil have also isolated this serotype from cattle (Bando et al, 2017;Dos Santos et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Serotypes O116:H21 ST58 and O168:H8 ST718 were the most represented; these have been previously isolated from cattle [ 48 , 49 , 50 ]. Furthermore, serotypes O26:H11, O91:H21, O113:H21, O116:H21, and O130:H11, characterized in this study, have also caused disease and human outbreaks [ 51 , 52 , 53 ]. For example, STEC O116:H21 was isolated in Argentina from ground beef [ 54 ] and cattle feces [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Chile, official reports indicate STEC O113 is one of the most frequent serogroups isolated from meats [ 9 ]. In Argentina, STEC O113 has been isolated from ground beef and cattle, and it has also caused human disease, rising as an emerging serotype in the country [ 53 , 54 ]. We also reported one strain of the Big Six groups: STEC O26:H11.…”
Section: Discussionmentioning
confidence: 99%